Decreasing Cell Population of Individual Candida Species Does Not Impair the Virulence of Candida albicans and Candida glabrata Mixed Biofilms - Li, Qianqian; Liu, Juanjuan; Shao, Jing; Da, Wenyue; Shi, Gaoxiang; Wang, Tianming; Wu, Daqiang; Wang, Changzhong (Frontiers in Microbiology, 2019)
Candida albicans and Candida glabrata are two commonly seen opportunistic fungi in clinical settings and usually co-isolated from the population inflicted with denture stomatitis and oropharyngeal candidiasis. Although C. albicans and C. glabrata mixed biofilm is deemed to possess enhanced virulence compared with their individual counterparts (especially C. albicans single biofilm), the relevant descriptions and experimental evidence on the relationship of Candida virulence with their individual cell number in mixed biofilms are contradictory and insufficient. In this study, two standard C. glabrata isolate and eight C. albicans ones were used to test the cell quantities in their 24- and 48-h single and mixed biofilms. A series of virulence factors including antifungal resistance to caspofungin, secreted aspartic proteinase (SAP) and phospholipase (PL) levels, efflux pump function and β-glucan exposure were evaluated. Through this study, the declines of individual cell counting were observed in the 24-h and 48-h Candida mixed biofilms compared with their single counterparts. However, the antifungal resistance to caspofungin, the secreted aspartic proteinase (SAP) and phospholipase (PL) levels, the rhodamine 6G efflux and the efflux-related gene expressions were increased significantly or kept unchanged accompanying with reduced β-glucan exposure in the mixed biofilms by comparison with the single counterparts. These results reveal that there is a competitive interaction between C. albicans and C. glabrata strains in their co-culture without at the expense of the mixed biofilm virulence. This study presents a deep insight into the interaction between C. albicans and C. glabrata and provides new clues to combat against fungal infections caused by Candida mixed biofilms.